Estilos de aprendizagem e educação a distância: perspectivas e contribuições - Kalatzis, Adriana Casale; Belhot, Renato Vairo (Revista Gestão da Produção Operações e Sistemas, 2007)
Taking into consideration the individual differences in learning and in the teaching modalities, this paper aimsat discussing the perspectives and contributions that the learning styles can provide to the Distance Educationmodality. It also attempts to identify how the Information and Communication Technologies (ICTs) can makefeasible the combination among different work dynamics in the Distance Education environment. Such combinationcan benefit the most diverse learning styles, since the ICT tools are essential to facilitate the teachingand learning processes of students and professors in the development of activities in Distance Education. In thissense, one can affirm that it is important to understand the need to be aware of the significant role of the learningstyles in distance teaching, since computer-based Distance Education enlarges the possibilities to developnew skills in the teaching and learning process.Keywords: Learning styles; Distance education; Information and communication technology.